Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Pada Pt. Silver Silk Tour dan Travel Pekanbaru - Hidayat, Rahmadani; Yusuf, Muhammad (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2022)
The purpose of this study was to determine the effect of work motivation on employee performance. The subjects of this research are employees. While the object in this study is the effect of work motivation on employee performance. Sources of data used in this study are primary data and secondary data. The sampling technique used was total sampling, while the data collection techniques used were questionnaires and documentation. The quantitative descriptive method was used to analyze the data. In analyzing quantitative data, a simple linear regression analysis was used where the calculation process used SPSS version 23 for windows. The results of this study indicate that work motivation on employee performance has a very strong relationship, it is known from the correlation coefficient of 90.8%, while the partial test results show that there is a significant influence between work motivation on employee performance, with a significance level. from 0.000 < 0.05. The contribution of work motivation to employee performance is known with a determination coefficient of 82% and the remaining 12% is influenced by other factors not included in this study. In general, it can be concluded that there is an influence between organizational culture on employee performance at PT. Silver Silk Tour & Travel Pekanbaru Head Office.